Organisation Structures of Chinese Family Businesses: a case study of recruitment & selection and retention in a Chinese family business - Ying, Jun (2009)
Chinese family businesses have been studied by abundant researchers in the early 1960s. Gordon Redding as one of these researchers carefully defines organisation structures of Chinese family businesses throughout his systematic investigations that were published in 1990, whereas recent statistics of Chinese family businesses in China show the different perspective against Redding (1990). Therefore, this research is to examine differences on organisation structures between Redding (1990) and an empirical finding in Shanghai, China. This research employs a qualitative research method to investigate recruitment & selection and retention in a Chinese family business in order to explore organisation structures in recent Chinese family businesses. The findings of this research reveal inconsistencies between Redding (1990) and actual performance of Chinese family businesses, while they fit in with Chen’s (2001) three transformation paths, and thus to present reasons and ways of changing on organisation structures within Chinese family businesses.